2010
DOI: 10.2478/v10042-009-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis vulgaris and digestive system disorders: is there a linkage?

Abstract: Psoriasis is well-known immune-mediated skin disease often associated with co-morbidities, including dyslipidaemia and obesity. Few reports imply that the disease might be also related to pathology of mucosal surfaces, especially that of the digestive system. The authors present a case of psoriasis and concurrent digestive system abnormalities, and review the literature regarding the topic. A 40-year-old man suffered from an exacerbation of exudative psoriasis for about 6 months. Topical antipsoriatics proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, in some genetically predisposed individuals, bacteria or fungi on the mucous membranes may lead to the activation of the local innate immune system and, in turn, induce an adaptive immune response [ 34 ]. These recent findings partially explain the presence of gastrointestinal symptoms in patients with psoriasis as well as coexistence with inflammatory bowel diseases [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 95%
“…However, in some genetically predisposed individuals, bacteria or fungi on the mucous membranes may lead to the activation of the local innate immune system and, in turn, induce an adaptive immune response [ 34 ]. These recent findings partially explain the presence of gastrointestinal symptoms in patients with psoriasis as well as coexistence with inflammatory bowel diseases [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 95%
“…[ 28 29 ] The pivotal mediators of inflammation in psoriasis, including tumor necrosis factor (TNF) -α, interleukin (IL)-1, IL-17, and IL-18, are also overexpressed in patients with pancreatitis and their expressions are related to the severity of pancreatic destruction and eventual mortality. [ 28 , 30 33 ] Mews et al showed that persistent activation of the stellate pancreatic cells by TNF-α and IL-1 could be a factor in the progression of CP. [ 34 35 ] In murine models, TNF-α has been shown to induce severe pancreatitis and be involved in subsequent pancreatic fibrosis by inducing TGF-β.…”
Section: Discussionmentioning
confidence: 99%